Cystic fibrosis transmembrane conductance regulator (CFTR) gene mutations in allergic bronchopulmonary aspergillosis - Miller, Patrice Weiner; Hamosh, Ada; Macek, Milan; Greenberger, Paul A; MacLean, James; Walden, Sandra M; Slavin, Raymond G; Cutting, GarryR (American journal of human genetics, 1996)
The etiology of allergic bronchopulmonary aspergillosis (ABPA) is not well understood. A clinical phenotype resembling the pulmonary disease seen in cystic fibrosis (CF) patients can occur in some individuals with ABPA. Reports of familial occurrence of ABPA and increased incidence in CF patients suggest a possible genetic basis for the disease. To test this possibility, the entire coding region of the cystic fibrosis transmembrane regulator (CFTR) gene was analyzed in 11 individuals who met strict criteria for the diagnosis of ABPA and had normal sweat electrolytes (< or = 40 mmol/liter). One patient carried two CF mutations (deltaF508/R347H), and five were found to carry one CF mutation (four deltaF508; one R117H). The frequency of the deltaF508 mutation in patients with ABPA was significantly higher than in 53 Caucasian patients with chronic bronchitis (P < .0003) and the general population (P < .003). These results suggest that CFTR plays an etiologic role in a subset of ABPA patients.
Keywords: mutace; dospělí; Cystic Fibrosis Transmembrane Conductance Regulator; heterozygot; Genotype; Female; Phenotype; Aspergillosis, Allergic Bronchopulmonary; bronchitida; Adult; ženské pohlaví; cystická fibróza; lidé; Heterozygote; genotyp; Bronchitis; protein CFTR; Mutation; Male; Cystic Fibrosis; chronická nemoc; lidé středního věku; fenotyp; mužské pohlaví; Chronic Disease; Middle Aged; aspergilóza alergická bronchopulmonální; Humans